Pemberdayaan Siswa SD Tentang Keterampilan Cuci Tangan di Purbowangi Buayan Kebumen - Rahmawati, Aziza; Wahyuni, Sri; Sulastri, Eni (Yayasan Inspirasi El Burhani, 2024)
Introduction: Efforts to change health behavior to support an increase in levels are carried out through a Clean and Healthy Living Behavior development program, one of which is washing hands. The low level of parental behavior in training children to wash their hands with soap before and after eating is the reason why it is important to wash their hands. Objective: The purpose of this service was to empower students to improve hand washing skills for students at Elementary School 4 Purbowangi Kebumen. Method: This public service was conducted by providing counseling using the correct hand washing demonstration method to 94 students, the activity steps include: the staff observes the hand washing skills of students before being given treatment (pretest), then provides counseling using a demonstration method about hand washing. The next step is for the service to observe the hand washing skills of students after being given treatment (posttest). Result: The results of this community service activity showed that the majority of participants were male, 51 students (54.3%), 33 (35.1%) aged at most 10 years. Hand washing skills before and after being given the intervention improved. This is evident from the results of the average hand washing skill before the demonstration was 41.0904 (poor) and the average hand washing skill after the demonstration was 96.2234 (very good). Conclusion: Activities to empower elementary school students regarding hand washing skills went smoothly and was able to improve the skills of all students in washing their hands.